Diagnostic and Feedback Behavior of German Pre-Service Teachers Regarding Argumentative Pupils' Texts in Geography Education - Saskia Steingrübl; Alexandra Budke (MDPI AG, 2024)
The study sheds light on the importance of diagnostic and feedback skills regarding argumentative pupils' texts for (prospective) teachers and the current state of research in this area. The importance of argumentation in geography education is undisputed, as geographical problems often require multi-layered solutions that can be analyzed, assessed and reflected upon by teachers and pupils through argumentation skills. Nevertheless, research findings reveal that both teachers and pupils often have limited argumentation skills, which poses a challenge for both. The present study investigates the attitudes and practices of prospective geography teachers regarding the diagnosis of and feedback on pupils' argumentative texts. Using a qualitative research design, twenty German pre-service teachers of geography were interviewed about their diagnostic and feedback experiences and asked to analyze and provide feedback on an argumentative pupil text. The results were evaluated using qualitative content analysis. In addition, a theoretical model for diagnosis was developed, which was used to analyze the pre-service teachers' diagnostic behavior. The criteria used by the pre-service teachers to evaluate the argumentative pupils' text were examined. The results show that the diagnosis often lacks the exploration of causes and the deduction of consequences, and that only a few subject-specific criteria were taken into account in the text assessment. In addition, the feedback was generally more positive than the diagnosis itself. The results offer insights into the design of diagnostic and feedback processes in geography education and provide impulses for (higher) education teaching and future research.